Ectoparasitos em pequenos mamíferos silvestres da estação experimental Rafael Fernandes, Rio Grande do Norte, Brasil - Pereira, Josivania Soares (Universidade Federal Rural do Semi-Árido, 2015)
Small wild mammals, including rodents and marsupials, have ecological and epidemiological importance for being prey and predators in ecological chains, hosts of ecto and endoparasites and pathogens reservoirs. In Northeast Brazil, only a few studies have evaluated the diversity of ectoparasites and their hosts in the Caatinga biome. This study aimed to identify the hosts and their ectoparasites, with morphometric analysis and chaetotaxy and to determine the rates of parasitic Prevalence, Abundance and Medium Intensity of ectoparasites collected from rodents and marsupials, proceeding from the Experimental Station Rafael Fernandes, Rio Grande do Norte, Brazil, at the Universidade Federal Rural do Semi-Árido (UFERSA). The animals were captured between January 2014 and February 2015, in a fragment of 26 hectares, divided into six equally spaced transects (20m). Tomahawk and Sherman traps were distributed in six consecutive nights of each month and in 100 capture stations. The captured animals were identified by morphology and submitted to ectoparasites collection. All the collected ectoparasites were classified based on morphometric characters, chaetotaxy and taxonomic keys, as well as DNA extraction, PCR and sequencing of the amplified products. 78 small mammals were captured, from which 69 were classified as Didelphimorphia order: Gracilinanus agilis (Burmeister, 1854) and Monodelphis domestica (Wagner, 1842); and nine Rodentia: Wiedomys Hershkovitz, 1959, Thrichomys Trouessart, 1880 and Rattus norvegicus Berkenhout, 1769. It was collected ectoparasites identified as: Amblyomma (Koch, 1844), Amblyomma parvum, Aragão 1908, Amblyomma auricularium (Conil, 1878), Ornithodoros mimon Kohls, Clifford e Jones 1969, Ornithodoros Kohls, Clifford e Jones 1837, Quadraseta Brennan, 1970, Eutrombicula Ewing, 1938, Metachiroecius Fain, 1996, Aeromychirus Fain, 1976, Amlistrophorus Fain, 1981, Radfordia Ewing, 1938, Listropsoralges aff. similis, Ornithonyssus pereirai (Fonseca, 1935), Tur lativentralis (Fonseca 1936), Polyplax spinulosa (Burmeister, 1839) and Eogyropus lenti lenti (Werneck 1936). As for the parasitic rates were noted that for the Ixodidae and Argasidae studied, M. domestica presented higher parasitism values for A. auricularium; G. agilis, O. mimon and Thrichomys sp., to A. parvum and A. auricularium. As for mites, the prevalence was the same in M. domestica and to all its studied Listrophoridae. Also for rodents, it was observerd the same prevalence rate for Laelapidae mites and Polyplacidae lice in the Thrichomys sp. All of those records of small mammals and ectoparasites shown are unprecedented to Mossoró, Rio Grande do Norte. This study supports evidences from the literature that ectoparasites use marsupials and wild rodents as hosts for immature stages. Justifies the importance of maintaining a legal reserve area in the Caatinga biome for preservation of these animals. In addition, this research increases knowledge about the occurrence of Acari, Phthiraptera and its ectoparasitic association with the wildlife in Northeast Brazil
Ectoparasites in small wild mammals at the Experimental Station Rafael Fernandes, Rio Grande Do Norte, Brazil
Keywords: ectoparasites; Tick; Marsupial; Louse; Rodent; Ectoparasitismo; Carrapato; Marsupial; Piolho; Roedor; CIENCIAS AGRARIAS::MEDICINA VETERINARIA